2008
DOI: 10.1158/1055-9965.epi-08-0075
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Chinese Restaurant Workers of Exposure to Cooking Oil Fumes: A Cautionary Note on Urinary 8-Hydroxy-2′-Deoxyguanosine

Abstract: This study evaluates oxidative DNA damage in workers who are exposed to cooking oil fumes (COFs) in Chinese restaurants. The study participants were 387 nonsmoking Chinese restaurant workers, 202 kitchen staff, and 185 service staff at 23 Chinese restaurants in Taiwan. Airborne particulate matter and particulate polycyclic aromatic hydrocarbon levels were monitored in kitchens and dining areas. Urinary 1-hydroxypyrene (1-OHP) was used as an internal dose of exposure to COFs, and urinary 8-hydroxy-2 ¶-deoxyguan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 40 publications
6
60
0
1
Order By: Relevance
“…Our results showed that nonsmoking female lung adenocarcinoma was closely related to cooking oil fumes exposure. There are studies in Shanghai, Taiwan, Hong Kong and other places reporting the significant association of lung cancer in women with expose to cooking oil fume (Zhong et al, 1999;Ko et al, 2000;Yu et al, 2006;Pan et al, 2008). Previous studies have shown that sugar, proteins, fat and amino acids can release some harmful substances, such as particulate matter (PM), polycyclic aromatic hydrocarbons, aromatic amines, nitro-PAHs, and aldehydes under the hightemperature treatment (Vainiotalo et al, 1993;Li et al, 1994;Wu et al, 1998;Chiang et al, 1999;Lund et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that nonsmoking female lung adenocarcinoma was closely related to cooking oil fumes exposure. There are studies in Shanghai, Taiwan, Hong Kong and other places reporting the significant association of lung cancer in women with expose to cooking oil fume (Zhong et al, 1999;Ko et al, 2000;Yu et al, 2006;Pan et al, 2008). Previous studies have shown that sugar, proteins, fat and amino acids can release some harmful substances, such as particulate matter (PM), polycyclic aromatic hydrocarbons, aromatic amines, nitro-PAHs, and aldehydes under the hightemperature treatment (Vainiotalo et al, 1993;Li et al, 1994;Wu et al, 1998;Chiang et al, 1999;Lund et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During the cooking, workers may expose to many cooking fumes, high radiation from microwaves, strong light from incandescent ovens, and infrared radiation (Yenugadhati et al, 2009;Santibanez et al, 2012). Cooking fumes are produced and released into the environment when food is fried or grilled using cooking oil at high temperatures (Pan et al, 2008;Santibanez et al, 2012). The degradation of sugar, the pyrolysis of proteins and amino acids, and the degradation of fat during the high-temperature treatment of food can generate harmful degradation products, such as particulate matter (PM), polycyclic aromatic hydrocarbons (PAH), aromatic amines, and aldehydes (Pan et al, 2008;Santibanez et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cooking fumes are produced and released into the environment when food is fried or grilled using cooking oil at high temperatures (Pan et al, 2008;Santibanez et al, 2012). The degradation of sugar, the pyrolysis of proteins and amino acids, and the degradation of fat during the high-temperature treatment of food can generate harmful degradation products, such as particulate matter (PM), polycyclic aromatic hydrocarbons (PAH), aromatic amines, and aldehydes (Pan et al, 2008;Santibanez et al, 2012). Those subjects may cause the reactive oxygen species in human body, and may further cause oxidative damage to nucleic acids, proteins, and lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFs at least contained 200 kinds of compounds, which could be divided into aldehydes, heterocyclic amines (HCAs), polycyclic aromatic hydrocarbons (PAHs), fat aerosols and particulate matters (PM) [6,7,[18][19][20]. Shields et al [21] investigated the effects of various appliances such as ovens, broilers and griddles on the production and composition of CFs.…”
Section: B Composition Of Cfsmentioning
confidence: 99%